PERBANDINGAN ESTIMASI ANGGARAN BIAYA DENGAN METODE SNI DAN BOW - Mahardika Rahmawan Putra; Nur Azizah Affandy (Litbang Pemas - Universitas Islam Lamongan, 2017)
The concept of drafting the Budget Plan (RAB) project is done based on an analysis of each constituent component for every work items on the entire project. This calculation analysis use two methods, SNI method and BOW method. This calculation uses the analysis of unit price in 2016. From the calculation, the analysis of unit prices in the construction of religious ministry office in Lamongan Regencyshows that the budget estimation using SNI method is more economical. SNI method has more economical budget in the amount of Rp. 709,743,313.65 compared to BOW method, amountedRp 1,759,104,217.65. The difference of those two methods is Rp. 1,049,360,904. This result occurs because the coefficient for SNI method is lower than the BOW method.